Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4815993
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic response of Fe-coated W tips in spin-polarized scanning tunneling microscopy

Abstract: We performed spin-polarized scanning tunneling spectroscopy on biatomic-layer-high Co nanoislands grown on Cu(111) in magnetic fields oriented normal to the sample surface, with Fe-coated W tips. Increasing the temperature from 10 to 30 K, we observe a reduced slope of the differential conductance around zero field. A quantitative analysis of the field- and temperature-dependent differential conductance data in the framework of superparamagnetism as described by a Langevin function gives an excellent descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…It is evident that the tip and its detailed apex configuration are central for performing reliable spin-resolved spectroscopy measurements (Phark et al, 2013). Recent experiments by combined atomic force microscopy and STM offer a venue to characterize tips and their apex configurations on the atomic scale, and corresponding experiments would improve the tip characterization considerably (Welker and Giessibl, 2012).…”
Section: Characterization and Control Of Magnetic Sp-stm Tipsmentioning
confidence: 99%
“…It is evident that the tip and its detailed apex configuration are central for performing reliable spin-resolved spectroscopy measurements (Phark et al, 2013). Recent experiments by combined atomic force microscopy and STM offer a venue to characterize tips and their apex configurations on the atomic scale, and corresponding experiments would improve the tip characterization considerably (Welker and Giessibl, 2012).…”
Section: Characterization and Control Of Magnetic Sp-stm Tipsmentioning
confidence: 99%
“…Our empirical observations tell us that the tip behavior is not conclusively determined by the macroscopic tip preparation. Rather, the tip response to the field is largely determined by microscopic changes at the tip apex [46,48].…”
Section: The Extraction Of Switching Fields and Spin Polarization Fromentioning
confidence: 99%
“…The sequential deposition leads to the formation of two different types of islands on the Cu substrate; Fe|Co island and isolated Fe island, both are BL high. STM and STS on an Fe|Co island revealed that the distinction between Co and two different Fe structural phases is possible by a difference in apparent heights and pronounced spectroscopic signatures in the differential conductance 26 . In order to obtain magnetic contrast, we used Cr/Co-coated W tips.…”
Section: Methodsmentioning
confidence: 99%
“…1; Supplementary Note 2), which indicates that the island does not present a measurable periodic magnetic order at 0 T 25 . Figure 2a,b shows the differential conductance images of pure Fe islands and a Co island in circumferential contact with an Fe BL rim (Fe|Co island) 26 (see also Methods section), respectively, where Co, Fe-a and Fe-b are identified by STS measurements (Supplementary Fig. 1; Supplementary Note 1).…”
Section: Spin-dependent Differential Conductance Of Fe Nanoislandsmentioning
confidence: 99%